Gut Microbiome and Common Variable Immunodeficiency: Few Certainties and Many Outstanding Questions - Varricchi, Gilda; Poto, Remo; Ianiro, Gianluca; Punziano, Alessandra; Marone, Gianni; Gasbarrini, Antonio; Spadaro, Giuseppe (Frontiers in Immunology, 2021)
Common variable immunodeficiency (CVID) is the most common symptomatic primary antibody immunodeficiency, characterized by reduced serum levels of IgG, IgA, and/or IgM. The vast majority of CVID patients have polygenic inheritance. Immune dysfunction in CVID can frequently involve the gastrointestinal tract and lung. Few studies have started to investigate the gut microbiota profile in CVID patients. Overall, the results suggest that in CVID patients there is a reduction of alpha and beta diversity compared to controls. In addition, these patients can exhibit increased plasma levels of lipopolysaccharide (LPS) and markers (sCD14 and sCD25) of systemic immune cell activation. CVID patients with enteropathy exhibit decreased IgA expression in duodenal tissue. Mouse models for CVID unsatisfactorily recapitulate the polygenic causes of human CVID. The molecular pathways by which gut microbiota contribute to systemic inflammation and possibly tumorigenesis in CVID patients remain poorly understood. Several fundamental questions concerning the relationships between gut microbiota and the development of chronic inflammatory conditions, autoimmune disorders or cancer in CVID patients remain unanswered. Moreover, it is unknown whether it is possible to modify the microbiome and the outcome of CVID patients through specific therapeutic interventions.